Effect of acetone and methanol environment on the electrical properties of Fe doped hydroxyapatite. Issue 3 (25th March 2021) - Singh, Brajendra; Singh, Priyanka; Siddiqui, Saiqua; Rajput, Parasmani; Gupta, Mukul
Abstract: We report huge change in impedance of Fe doped hydroxyapatite Ca9.9 Fe0.1 (PO4 )6 (OH)2 in presence of methanol and acetone environment while parent hydroxyapatite Ca10 (PO4 )6 (OH)2 shows only nominal change. Parent and Fe doped hydroxyapatite Ca1−x Fex (PO4 )6 (OH)2 (0 ≤ x ≤ 0.3) samples were prepared by wet chemical method. All the samples are found in single phase using X‐ray diffraction (XRD), and they are crystallized in hexagonal structure. Fe K‐edge X‐ray absorption near edge structure (XANES) spectra show the presence of mixed‐valence states (Fe 2+ and Fe 3+ ) in Ca9.9 Fe0.1 (PO4 )6 (OH)2 sample while Fe is present in Fe 3+ valence state in Ca9.7 Fe0.3 (PO4 )6 (OH)2 sample. Fe doped composition Ca9.9 Fe0.1 (PO4 )6 (OH)2 has shown the change in impedance (response) 80% in presence of 50 ppm methanol concentration and 238% for 500 ppm methanol concentration. Ca9.9 Fe0.1 (PO4 )6 (OH)2 has shown 92% response for 50 ppm acetone concentration and 537% response for 500 ppm acetone concentration. Analysis of response (change in impedance) using Freundlich adsorption isotherm equation has shown the physical and chemical type of adsorption for methanol while only physical adsorption for acetone is found in Ca9.9 Fe0.1 (PO4 )6 (OH)2 . Abstract : Fe doped composition Ca9.9Fe0.1(PO4)6(OH)2 showed change in impedance (response) 80% for 50 ppm concentration of methanol and 92% for 50 ppm concentration of acetone. Parent composition does not show any significance change in the presence of methanol and acetone.